Perencanaan Alat Uji Impact Type Charpy Kapasitas 10 Joule - Saktiawan, Saktiawan; Endriatno, Nanang; Imran, Al Ichlas (Enthalpy : Jurnal Ilmiah Mahasiswa Teknik Mesin, 2020)
In  the  implementation  of  construction  and  material  engineering,  the  choice  of materials  for  metal  material  needs  is  very  important.  The  research  objectives were planning the pendulum, swing shaft, the frame for the Charpy type impact test,  and  planning  the  test  specimen  holder.  The  research  method  includes planning  the  pendulum,  shaft,  arm,  bearing,  pole  frame  and  specimen  holder (anvil), as well as selecting materials and calculating the strength of the materials. The results of the research. The impact test tool uses a pendulum made of steel ST 37 with a pendulum length = 0.345 mm, volume = 213 mm3, mass = 1.67 kg, in the planning of the shaft, with the results of the planning calculation obtained the diameter of the shaft = 25.4 mm, while the moment torque obtained = 577,219 kg mm, in the planning of the Charpy type impact test, the frame uses C-profile steel with  a  size  of  125  x  65,  the  material  is  chosen  because  its  width  exceeds  the bearing holder, for tangsial force = 28,951 N, bending moment = 5240.1 N mm , cross-sectional  modulus  =  109.169  mm3,  the  specimen  holder  planning  must exceed  the  specimen  width  itself  so  that  the  specimen  can  be  placed  properly, the allowance = 1.206 mm2 and the planning of the impak test tool for the 10 J tool can be used to test plastic materials with an impact energy below 10 J, with a height of 610 ± 2 mm. Keywords:  Construction,  Materials  Engineering,  Metal  Materials,  Iron,  Steel, Impak.